Deferasirox, an oral iron chelator, prevents hepatocarcinogenesis and adverse effects of sorafenib - Yamamoto, Naoki (J Clin Biochem Nutr, 2016)
Although sorafenib is expected to have a chemopreventive effect on hepatocellular carcinoma (HCC) recurrence, there are limitations to its use because of adverse effects, including effects on liver function. We have reported that the iron chelator, deferoxamine can prevent liver fibrosis and preneoplastic lesions. We investigated the influence of administering a new oral iron chelator, deferasirox (DFX), on the effects of sorafenib. We used the choline-deficient l-amino acid-defined (CDAA) diet-induced rat liver fibrosis and HCC model. We divided rats into four groups: CDAA diet only (control group), CDAA diet with sorafenib (sorafenib group), CDAA diet with DFX (DFX group), and CDAA diet with DFX and sorafenib (DFX + sorafenib group). Liver fibrosis and development of preneoplastic lesions were assessed. In addition, we assessed adverse effects such as changes in body and liver weight, skin damage (eruption, dryness, and hair loss), which is defined as hand-foot skin syndrome, in the sorafenib and DFX + sorafenib groups. The combination of DFX + sorafenib markedly prevented liver fibrosis and preneoplastic lesions better than the other treatments. Furthermore, the combination therapy significantly decreased adverse effects compared with the sorafenib group. In conclusion, the combination therapy with DFX and sorafenib may be a useful adjuvant therapy to prevent recurrence after curative treatment of HCC.